2023
DOI: 10.1039/d2cs00999d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing biomaterials in living organisms

Xiangyang Zhang,
Junxia Wang,
Ying Zhang
et al.

Abstract: Synthesizing biomaterials from building blocks in living organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 220 publications
(334 reference statements)
0
7
0
Order By: Relevance
“…Peptide assemblies have emerged as a new class of biomaterials and have received increased research attention over the last two decades. Since the seminal works demonstrated the applications of peptide assemblies in tissue engineering , and the report of exceptional self-assembling ability of short peptides, peptide assemblies have been explored for a wide range of applications, such as drug delivery, cancer therapy, optoelectronics, cell cultures, , antibacterial, immunomodulation, molecular imaging, , and protein mimics. , Being encouraged by these rapid advances, we and Ulijn et al have shown the use of enzymatic reactions for generating peptide assemblies as a type enzyme-responsive biomaterials. Specifically, we have been developing phosphopeptides as substrates of alkaline phosphatase (ALP) to generate peptide assemblies inside cancer cells as an alternative approach to target drug-resistant and immunosuppressive tumors . Recently, we have found that a phosphopentapeptide [NBD-LLLL- p Y ( 1 )] is able to undergo enzyme-instructed self-assembly (EISA) ,, and accumulate intranuclearly for killing cells that overexpress ALP, such as human induced pluripotent stem cells (iPSC) or osteosarcoma cells (e.g., Saos2) .…”
Section: Introductionmentioning
confidence: 99%
“…Peptide assemblies have emerged as a new class of biomaterials and have received increased research attention over the last two decades. Since the seminal works demonstrated the applications of peptide assemblies in tissue engineering , and the report of exceptional self-assembling ability of short peptides, peptide assemblies have been explored for a wide range of applications, such as drug delivery, cancer therapy, optoelectronics, cell cultures, , antibacterial, immunomodulation, molecular imaging, , and protein mimics. , Being encouraged by these rapid advances, we and Ulijn et al have shown the use of enzymatic reactions for generating peptide assemblies as a type enzyme-responsive biomaterials. Specifically, we have been developing phosphopeptides as substrates of alkaline phosphatase (ALP) to generate peptide assemblies inside cancer cells as an alternative approach to target drug-resistant and immunosuppressive tumors . Recently, we have found that a phosphopentapeptide [NBD-LLLL- p Y ( 1 )] is able to undergo enzyme-instructed self-assembly (EISA) ,, and accumulate intranuclearly for killing cells that overexpress ALP, such as human induced pluripotent stem cells (iPSC) or osteosarcoma cells (e.g., Saos2) .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous molecular probes have been developed for the imaging and/or treatment of tumors or other diseases in vivo based on the stimuli-triggered molecular in situ self-assembly strategy. These self-assembly molecular probes can be responsive to different stimuli, such as pH, , reactive oxygen species (ROS), , biothiols, , light, , temperature, , ultrasound (US), , enzymes, , antigens, , and nucleic acids. , Among these stimuli, enzymes represent a type of important molecular triggers due to their crucial roles in controlling various biological processes. It has been recognized that aberrant expression of enzymes is intricately linked to metabolic disorders, genetic diseases, and impaired physiological functions. Precise in vivo detection of their activity is significant for the diagnosis of tumors and other diseases. The enzymatic molecular in situ self-assembly (E-MISA) strategy has shown promise for molecular imaging and theranostics .…”
Section: Introductionmentioning
confidence: 99%
“…Radical chain growth polymerization leads to linear polymers and can be carried out under cytocompatible conditions on living cells. 20–22 For example, polymer chains were grafted from living yeast cells through copper-catalysed atom transfer radical polymerization (ATRP), 13 or photoinduced electron transfer-reversible addition–fragmentation chain-transfer polymerization (PET RAFT). 23,24 However, the conditions used were relatively harsh and not easily scalable.…”
Section: Introductionmentioning
confidence: 99%